1950
DOI: 10.1085/jgp.33.5.475
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Metabolism of Schistosoma Mansoni

Abstract: In contrast to vertebrates and to bacteria relatively little is known about the metabolism of invertebrates (1). For a better understanding of comparative biochemistry information about this subject is required. Furthermore, investigations of the biochemical characteristics of parasitic invertebrates will reveal metabolic reactions essential for survival of these organisms. Information obtained from such studies will make it possible to search for non-toxic inhibitors of essential metabolic reactions and event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
0
3

Year Published

1952
1952
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(103 citation statements)
references
References 5 publications
3
97
0
3
Order By: Relevance
“…However, role of oxygen in adult metabolism is less well defined. While it has been reported that no increase in lactate production is seen in worms incubated under anaerobic conditions (Bueding, 1950), other studies indicate that oxygen may be essential, especially if worms are to maintain high egg production levels, and that adult worms possess a functional tricarboxcylic acid cycle and respiratory chain (Coles, 1972). Profiling SAGE tags for the tricarboxcylic acid enzyme, succinate dehydrogenase, and the terminal oxidase beta subunit clearly indicate that the expression of genes encoding enzymes of oxidative respiration is equal or higher in mammalian-stage parasites than in snail-stage parasites (Fig.…”
Section: Expression Analysismentioning
confidence: 92%
“…However, role of oxygen in adult metabolism is less well defined. While it has been reported that no increase in lactate production is seen in worms incubated under anaerobic conditions (Bueding, 1950), other studies indicate that oxygen may be essential, especially if worms are to maintain high egg production levels, and that adult worms possess a functional tricarboxcylic acid cycle and respiratory chain (Coles, 1972). Profiling SAGE tags for the tricarboxcylic acid enzyme, succinate dehydrogenase, and the terminal oxidase beta subunit clearly indicate that the expression of genes encoding enzymes of oxidative respiration is equal or higher in mammalian-stage parasites than in snail-stage parasites (Fig.…”
Section: Expression Analysismentioning
confidence: 92%
“…In enzymatic studies, Bueding (1950) found that schistosome survival and reproduction depend directly on the absorption and utilization of the vertebrate host's carbohydrates as a of source energy, in a quantity of glucose equal to 20% of their weight per hour. The parasite metabolizes glucose by the Embden-Meyerhoff pathway, mainly under anaerobic conditions BUEDING, 1953BUEDING, , 1954BUEDING;MacKINNON, 1955).…”
Section: Introductionmentioning
confidence: 99%
“…Heart FABP is expressed at high levels in the myocardium, associated with ß-oxidation to generate power to the muscle (17). Although Sm14 has a higher phylogenetic relationship to heart FABP, it is known that S. mansoni is unable to use lipids as a power source (18,19).…”
mentioning
confidence: 99%